Jakten på koncentration - Från teori till idrott - Jansson, J. (2005)
When athletes and coaches discuss reasons for success or failure the word concentration has an important role. Likewise, in sport research, the term attention tends to have the same central position. This notion gives the impression that everyone seems to know what concentration is and how it affects sport performances. However, the many theories in cognitive psychology are not primarily designed to be applied in the setting of sport and exercise, and thus have little or no validity in that field. Instead of applying scientific knowledge, the field of sport enhancement often utilizes myths and folklore as bases for practice and exercise.